Intergroup Contact and White Racial Apathy: Findings from the National Study of Youth and Religion (NSYR). (December 2022) - Brown, Tony N.; Bento, Asia; Culver, Julian; Casarez, Raul S.; Duffy, Horace J.
Scholars theorize racial apathy is one form contemporary white racial prejudice takes. Racial apathy signals not caring about racial inequality. Invoking intergroup contact theory, we hypothesize interracial contact would predict less racial apathy among whites. To test our hypothesis, we analyze survey data from white teenagers participating in the 2003 National Study of Youth and Religion (NSYR). We find interracial contact matters and its inclusion improves model fit over and above previously specified correlates. Specifically, interracial friendship and dating, and having a different race mentor predict the tendency to care about racial equality. Furthermore, any interracial contact and a count of interracial contact experiences across five settings, respectively, predict less racial apathy. We encourage scholars to investigate further the sociological significance of racial apathy and its correlates, including interracial contact.